COMPARING THE HIGH AND LOW ACHIEVER STUDENTS DIFFICULTIES IN LEARNING WRITING DURING REMOTE LEARNING - Lestari Setyowati; Aqidatul Mujaddidah; Sony Sukmawan; Ana Ahsana El-Sulukiyyah (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2020)
Writing in English is very important for every student who learns English as a foreign language (EFL). With good writing skills, information can be conveyed well to readers. Yet, EFL students often find difficulties in writing by using English as a target language, especially during the pandemic of COVID 19. This paper aims to investigate some problems faced by the students in their learning of writing during the pandemic of COVD 19. The design of the study is a case study. The instruments to obtain the data were interviews and documents. The subjects of the study were three high achiever students and three low achiever students who joined the writing course in the English Education Study Program in the University of PGRI Wiranegara. They were chosen based on their writing achievements. The finding shows that the high achiever students problems are more on the technical problems (the internet connection, bad signals, and family distractions during online learning). For them the technical problems would lead to other issues such as materials comprehension and task accomplishment. The low achievers have more problems in generating ideas for all type of writing. The study also reveals that the low achievers have more time management problems and more language problems. Interestingly, they share the same solutions. The solutions are 1) to read more sources to get ideas and to help them write; 2) to boost moods before writing by reading a lot, listening to music, and watching movies; 3) to ask friends and lecturers to help understand the materials and tasks; and 3) to use writing tools application to solve the writing problems particularly in vocabulary and grammar.